Skip beat!. 25 - Nakamura, Yoshiki (Shojo beat manga., 2011)
"Kyoko's Valentine's battle with Reino has finally gained her Sho's attention-- but now it's the last thing she wants! Sho is determined to make her obsessed with him, and shows up on set with an over-the-top gift to taunt her. But when Kyoko explains her true relationship with Reino, Sho makes an inexcusable move. Has he undone her years of healing in one fell swoop?!"--Amazon.com.